2021
DOI: 10.1177/1060028021996337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dipeptidyl Peptidase-IV Inhibitor Use in Hospitalized Patients With Diabetes

Abstract: Background: Glycemic control within goal blood glucose (BG) ranges is essential to minimize hospital complications for patients with type 2 diabetes mellitus (T2DM). Optimal treatment in the non–intensive care unit (ICU) setting includes a basal insulin containing regimen. Dipeptidyl peptidase-IV (DPP-IV) inhibitors have minimal hypoglycemia incidence and may be an appropriate bolus insulin replacement in the inpatient setting. Objective: To determine the effect of basal insulin plus DPP-IV inhibitor compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Inhibition of DPP4 with gliptins stimulate angiogenesis and might help organ repair [26]. Petite et al found, in a cohort of hospitalized patients with diabetes a significant decrease in mean daily glycaemia and hospital length of stay in patients treated with a basal insulin plus DPP-IV inhibitor regimen compared to patients treated only with a basal plus bolus insulin [27]. While this secondary result should be interpretated with caution, pre-admission inhibition of DPP-4 might play a beneficial role in acute patients in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of DPP4 with gliptins stimulate angiogenesis and might help organ repair [26]. Petite et al found, in a cohort of hospitalized patients with diabetes a significant decrease in mean daily glycaemia and hospital length of stay in patients treated with a basal insulin plus DPP-IV inhibitor regimen compared to patients treated only with a basal plus bolus insulin [27]. While this secondary result should be interpretated with caution, pre-admission inhibition of DPP-4 might play a beneficial role in acute patients in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-IV has a variety of substrates including assisting in chemokines, growth factors, and peptides. In addition to its primary role in the regulation of glucose metabolism, it is classified as an oral diabetic medication through incretin hormones in gut that responsible for glucose homeostasis after oral food intake and approved by the FDA to treat type 2 diabetes mellitus in adults [21]. Besides the major role by DPP-III and -IV inhibitors, milk peptide also contains biological potentials for CaMPDE inhibitor, antidiabetic, stimulating vasoactive substance release, peptide stimulating mucin secretion, glucose uptake stimulating peptide, IOP Publishing doi:10.1088/1755-1315/1246/1/012039 6 and also regulating peptide in stomach mucosal membrane activity, regulator of phosphoglycerate kinase activity.…”
Section: Metabolic Healthmentioning
confidence: 99%
“…Estudios observacionales han mostrado resultados similares a los ensayos clínicos en la eficacia y seguridad para los inhibidores de la DPP-4 en el ámbito hospitalario. [23][24][25][26] Con respecto de la seguridad con este grupo de medicamentos, saxagliptina y alogliptina han sido asociados con un incremento en las hospitalizaciones por falla cardiaca, por lo que su uso en pacientes con cardiopatía preexistente debe evitarse. 27…”
Section: Inhibidores De La Dipeptidil-peptidasa-4unclassified